The role of strategic cooperation in achieving strategic sovereignty - Mahmoud Mohammed Amin Al-Bashqali; Hakmat Rashid Sultan (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The study aims at identifying the role of strategic cooperation through its fields including; education, scientific research, community service and other activities for the sake of achieving strategic sovereignty. This can be achieved through the dimensions such as (the influence spots, competitive pressure and competitive formation). In order to achieve the aim of this study, a number of questions raised such as: Is the leadership of the universities under the study familiarized with the concept of strategic cooperation and strategic sovereignty? What is the nature of the relationship of correlation and influence between strategic cooperation and strategic sovereignty in the universities? Are the surveyed universities differ in their focus on the variables of the study? Are there significant differences between the sample and the variables of the study based on their different demographic characteristics? The significant of the study lies in identifying the levels of strategic sovereignty and to explain the role of strategic cooperation in achieving it. To achieve the aim of the current study, four main hypotheses were developed. The study was based on an inductive method (descriptive analytical). The data were collected by means of a questionnaire and distributed to a random sample of (200) participants representing administrative leaders in the surveyed universities. Data were statistically analyzed by statistical package (SPSS: V. 22). The results of the study showed a significant correlation between strategic cooperation and strategic sovereignty at the macro level of the respondent sample. Moreover, it was found that there is a significant influence relationships for strategic cooperation in strategic sovereignty at the macro level of the respondent sample. The universities under study showed the variety in terms of their adoption of strategic improvisation. The study presented a number of suggestions, the most important are: To develop the strategic cooperation relations between the investigated universities and also to establish joint training programs with abroad universities in the training of teaching staff.